Declining diversity in abandoned grasslands of the carpathian mountains: do dominant species matter? - Anna Mária Csergő (Public Library of Science (PLoS), 2013)
Traditional haymaking has created exceptionally high levels of plant species diversity in semi-natural grasslands of the Carpathian Mountains (Romania), the maintenance of which is jeopardized by recent abandonment and subsequent vegetation succession. We tested the hypothesis that the different life history strategies of dominant grasses cause different patterns of diversity loss after abandonment of traditional haymaking in two types of meadow. Although diversity loss rate was not significantly different, the mechanism of loss depended on the life history of dominant species. In meadows co-dominated by competitive stress-tolerant ruderals, diversity loss occurred following the suppression of dominant grasses by tall forbs, whereas in meadows dominated by a stress-tolerant competitor, diversity loss resulted from increased abundance and biomass of the dominant grass. We conclude that management for species conservation in abandoned grasslands should manipulate the functional turnover in communities where the dominant species is a weaker competitor, and abundance and biomass of dominant species in communities where the dominant species is the stronger competitor.